Adhesive sheet roll
By winding the adhesive sheet with the first film, the first adhesive layer and the second film on the core material of an appropriate diameter with the first film side as the outer side, the wrinkle problem in the winding body of the adhesive sheet is solved, and the wrinkle problem in the winding body of the adhesive sheet is realized The excellent appearance of the adhesive sheet and the improvement of product performance.
Patent Information
- Application Number
- CN202010761033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-07-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-07-31
AI Technical Summary
Wrinkle problems often occur in the winding body of the adhesive sheet, which affects the appearance and performance of the product.
Adhesive sheets having a first film, a first adhesive layer and a second film are used, and the first film side is wound on a core material with a diameter of 180 mm or more and 800 mm or less in such a way that the second film is secured. The side surface of the first adhesive layer has not been peeled off.
It effectively inhibits the generation of wrinkles on the adhesive sheet, ensures the excellent appearance of the adhesive sheet, and improves the performance of the product.
Smart Images

Figure CN112409935B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet roll obtained by winding an adhesive sheet including a first film, a first adhesive layer and a second film, the second film not being a release sheet, around a core material with the first film-side surface facing outward. Background Art
[0002] The adhesive sheet having at least an adhesive layer is usually manufactured in the form of a long strip. Furthermore, the adhesive sheet manufactured in the form of a long strip is usually wound on a core material during manufacturing to form an adhesive sheet roll. The adhesive sheet roll manufactured in this way is also transported, stored, etc. in this form.
[0003] When manufacturing a predetermined product, an adhesive sheet may be used as a material or a process sheet, and an apparatus used for such manufacturing is generally capable of manufacturing the product while unwinding the adhesive sheet from the adhesive sheet roll as described above.
[0004] As an example of manufacturing a predetermined product using an adhesive sheet roll, Patent Document 1 discloses a method for manufacturing an optical display device by unwinding a predetermined amount of film from a roll-shaped raw material having a polarizer, an adhesive layer, and a release film, wherein the polarizer has a polarizing film and a polarizer protective film.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5801027 Summary of the invention
[0008] Technical Problems to be Solved by the Invention
[0009] However, in the adhesive sheet roll, sometimes there is a problem of appearance such as many wrinkles on the unwound adhesive sheet. Such a problem of appearance of the adhesive sheet not only damages the appearance of the product obtained by using the adhesive sheet, but also sometimes has a negative impact on the performance of the product.
[0010] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an adhesive sheet roll that can unwind an adhesive sheet having an excellent appearance.
[0011] Technical means to solve technical problems
[0012] In order to achieve the above-mentioned purpose, first, the present invention provides an adhesive sheet roll, which is formed by winding a long adhesive sheet having a first film, a first adhesive layer stacked on a single side of the first film, and a second film stacked on the side of the first adhesive layer opposite to the first film, on a cylindrical or cylindrical core material in a manner such that the surface on the first film side is the outer side, and the adhesive sheet roll is characterized in that the diameter of the core material is greater than 180 mm and less than 800 mm, and the surface of the second film on the first adhesive layer side has not been subjected to peeling treatment (Invention 1).
[0013] In the adhesive sheet roll of the above invention (Invention 1), by winding the adhesive sheet around the core material having the above diameter, an adhesive sheet having a good appearance and with wrinkles suppressed can be unwound.
[0014] In the above invention (Invention 1), it is preferable that the thickness of the first film is equal to or less than the thickness of the second film (Invention 2).
[0015] In the above inventions (Inventions 1 and 2), it is preferred that the peeling force when the first film is peeled off from the laminate of the first adhesive layer and the second film is 10 mN / 25 mm or more and 2000 mN / 25 mm or less (Invention 3).
[0016] In the above inventions (Inventions 1 to 3), the adhesive sheet preferably comprises: a second adhesive layer laminated on the side of the second film opposite to the first adhesive layer; and a third film laminated on the side of the second adhesive layer opposite to the second film (Invention 4).
[0017] In the above invention (Invention 4), it is preferred that the laminate of the third film and the second adhesive layer has an adhesive force to soda lime glass of 0.01 N / 25 mm or more and 20 N / 25 mm or less (Invention 5).
[0018] In the above inventions (Inventions 1 to 5), the storage elastic modulus of the first adhesive layer at 23° C. is preferably 0.001 MPa or more and 1.00 MPa or less (Invention 6).
[0019] Effects of the Invention
[0020] According to the adhesive sheet roll of the present invention, an adhesive sheet having an excellent appearance can be unwound. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a perspective view of a pressure-sensitive adhesive sheet roll according to one embodiment of the present invention.
[0022] Figure 2 This is a cross-sectional view of an adhesive sheet constituting an adhesive sheet roll according to one embodiment of the present invention.
[0023] Description of Reference Numerals
[0024] 1: adhesive sheet roll; 10: adhesive sheet; 11: first film; 12: first adhesive layer; 13: second film; 14: second adhesive layer; 15: third film; 20: core material. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described.
[0026] A perspective view of an adhesive sheet roll according to an embodiment of the present invention is shown in Figure 1 .like Figure 1 As shown, the adhesive sheet roll 1 of the present embodiment is formed by winding a long adhesive sheet 10 around a columnar or cylindrical core material 20 .
[0027] also, Figure 2 , a cross-sectional view of the adhesive sheet 10 of the present embodiment is shown. The adhesive sheet 10 of the present embodiment includes a first film 11, a first adhesive layer 12 laminated on one side of the first film 11, and a second film 13 laminated on the side of the first adhesive layer 12 opposite to the first film 11. Figure 2 As shown, the adhesive sheet 10 of this embodiment preferably further includes a second adhesive layer 14 laminated on the side of the second film 13 opposite to the first adhesive layer 12 , and a third film 15 laminated on the side of the second adhesive layer 14 opposite to the second film 13 .
[0028] The adhesive sheet roll 1 of the present embodiment is formed by winding the adhesive sheet 10 on the core material 20 with the surface on the first film 11 side thereof facing the outside. In addition, the surface on the first adhesive layer 12 side of the second film 13 is not subjected to a release treatment. That is, in the adhesive sheet roll 1 of the present embodiment, the second film 13 is not a release sheet.
[0029] In the adhesive sheet roll 1 of the present embodiment, the diameter of the core material 20 is greater than 180 mm and less than 800 mm. Thus, in the adhesive sheet roll 1 of the present embodiment, since the adhesive sheet 10 is wound on the core material 20 having a larger diameter, the adhesive sheet 10 with wrinkles suppressed can be unwound. That is, according to the adhesive sheet roll 1 of the present embodiment, an adhesive sheet 10 having a good appearance can be unwound. In addition, in the present specification, when the core material 20 is cylindrical, the diameter of the core material 20 refers to the outer diameter of the cylinder.
[0030] In the present specification, wrinkles generated in an adhesive sheet unwound from an adhesive sheet roll refer to any of deformation wrinkles generated when at least a portion of the adhesive sheet is deformed and folds generated when the adhesive sheet is bent.
[0031] In addition, it is speculated that the above-mentioned wrinkles are usually generated on the second film located on the inner side of the winding when the adhesive sheet winding body is manufactured or during subsequent storage, and will also spread to the first adhesive layer. However, since the tension of unwinding is applied to the second film when the adhesive sheet is unwound from the adhesive sheet winding body, and its restoring force as a film is large, the wrinkles of the second film tend to disappear. Different from this, the wrinkles of the first adhesive layer will not disappear due to unwinding, and are likely to remain on the unwound adhesive sheet. The adhesive sheet winding body 1 of this embodiment can well suppress the generation of wrinkles generated on the adhesive sheet 10, including such wrinkles remaining on the first adhesive layer.
[0032] The use form of the adhesive sheet 10 of the present embodiment is not limited, and the following use forms can be typically listed. First, the first film 11 is peeled off from the adhesive sheet 10 unwound by the adhesive sheet winding body 1. Then, for the laminated body of the second film 13 and the first adhesive layer 12 thus obtained, the surface of the first adhesive layer 12 side is attached to the adherend. When the adhesive sheet 10 has the second adhesive layer 14 and the third film 15, the laminated body of the second adhesive layer 14 and the third film 15 can be used as a protective film for protecting the second film 13. Such a protective film can be peeled off from the second film 13 at any time.
[0033] 1. Structure of adhesive sheet roll
[0034] (1) First film
[0035] In the adhesive sheet roll 1 of the present embodiment, the material of the first film 11 is not particularly limited. For example, the first film 11 may be made of a resin sheet containing a resin material as a main component, or may be made of a paper material.
[0036] As the resin component of the resin sheet, there can be listed polyolefins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-norbornene copolymer, norbornene resin, polyesters such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyvinyl chloride, vinyl chloride copolymers, polyimide, polyetherimide, polycarbonate, polyphenylene sulfide, liquid crystal polymers, etc. These resin sheets can be sheets consisting of a single layer, or sheets obtained by stacking multiple layers of the same or different types. Among the above, polyethylene terephthalate film is preferred.
[0037] Specific examples of the first film 11 made of a paper material include paper base materials such as glassine paper, coated paper, and high-quality paper, and laminated paper obtained by laminating a thermoplastic resin such as polyethylene on the above paper base materials.
[0038] The first film 11 is preferably a release sheet obtained by subjecting one side (particularly the side in contact with the first adhesive layer 12) of a sheet made of the above-mentioned resin sheet or paper material to a release treatment. Examples of the release agent used for the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.
[0039] The thickness of the first film 11 of the adhesive sheet roll 1 of the present embodiment is preferably less than the thickness of the second film 13. In this way, by making the thickness of the first film 11 located on the outside of the roll the same as or thinner than the thickness of the second film 13 located on the inside of the roll, it is easy to ease the winding pressure applied to the second film 13. As a result, the generation of wrinkles (especially the generation of wrinkles in the second film 13) in the adhesive sheet 10 unwound from the adhesive sheet roll 1 can be effectively suppressed.
[0040] From the perspective of easily achieving the above-mentioned thickness relationship between the first film 11 and the second film 13, the thickness of the first film 11 is preferably 20 μm or more, particularly preferably 30 μm or more, and further preferably 40 μm or more. In addition, the thickness of the first film 11 is preferably 150 μm or less, more preferably 100 μm or less, particularly preferably 80 μm or less, and further preferably 70 μm or less.
[0041] The Young's modulus of the first film 11 at 23°C is preferably 0.01 GPa or more, more preferably 0.1 GPa or more, particularly preferably 1 GPa or more, and further preferably 3 GPa or more. In addition, the Young's modulus is preferably 20 GPa or less, particularly preferably 10 GPa or less, and further preferably 5 GPa or less. By making the Young's modulus of the first film 11 at 23°C to be 0.01 GPa or more, the first film 11 has a predetermined strength, and the operability of the adhesive sheet 10 is more excellent. In addition, by making the Young's modulus of the first film 11 at 23°C to be 20 GPa or less, the winding pressure caused by the first film 11 to the second film 13 during winding is reduced, and it is easier to suppress the generation of wrinkles in the adhesive sheet 10. In addition, the Young's modulus in the specification of this application is a value obtained by measuring based on JIS K7161: 2014, and more specifically, it is a value obtained by measuring using a universal tensile tester at 23°C, 50% RH, and a tensile speed of 200 mm / min.
[0042] (2) First Adhesive Layer
[0043] The adhesive constituting the first adhesive layer 12 in the present embodiment is not particularly limited as long as it can achieve the required adhesive force, and can be appropriately selected according to the purpose. For example, the adhesive constituting the first adhesive layer 12 can be any one of acrylic adhesive, silicone adhesive, rubber adhesive, urethane adhesive, polyester adhesive, polyvinyl ether adhesive, etc. In addition, the above-mentioned adhesive can be any one of emulsion type, solvent type or solvent-free type, and can also be any one of cross-linked type or non-cross-linked type. Among them, from the perspective of having sufficient transparency and easily exerting the required adhesive force, as the adhesive constituting the first adhesive layer 12 in the present embodiment, it is preferred to use acrylic adhesive.
[0044] In addition, the adhesive constituting the first adhesive layer 12 may be an adhesive that is curable by active energy rays or an adhesive that is not curable by active energy rays. An adhesive that is curable by active energy rays refers to an adhesive that is curable by active energy rays in the stage of being used as an adhesive (for example, the stage of attaching the adhesive layer composed of the adhesive to the adherend). In the present embodiment, it refers to the situation in which the first adhesive layer 12 is curable by active energy rays in the state of the adhesive sheet roll 1. In addition, the concept of an adhesive that is curable by active energy rays also includes the following adhesives, that is, an adhesive in a so-called semi-cured (B stage) state that is optionally cured by active energy rays in the stage of manufacturing the adhesive.
[0045] On the other hand, a non-active energy ray-curable adhesive refers to an adhesive that has completed active energy ray curing and lost its active energy ray curability at the stage of being used as an adhesive, or an adhesive that has no active energy ray curability from the beginning.
[0046] Among them, compared with the non-active energy ray-curable adhesive, the cohesive force of the adhesive layer of the active energy ray-curable adhesive is generally low and soft. Therefore, when manufacturing the roll, the active energy ray-curable adhesive has a low ability to resist the deformation of the second film 13 and tends to easily generate wrinkles. Even when using such an adhesive that is difficult to suppress wrinkles, the adhesive sheet roll 1 of this embodiment can fully suppress the generation of wrinkles.
[0047] In addition, by using an active energy ray-curable adhesive, the adhesive sheet 10 of the present embodiment is suitable for being attached to an adherend having a step difference on the surface. That is, the adhesive sheet 10 of the present embodiment can attach the first adhesive layer 12 to the adherend in a relatively soft state with active energy ray curability, so that the first adhesive layer 12 can follow the step difference well. Then, by performing active energy ray curing, the cohesive force of the first adhesive layer 12 can be fully improved. Thus, even if the adhesive sheet 10 is placed under high temperature and high humidity conditions in a state where the cured first adhesive layer 12 is attached to the adherend, bubbles, floating, peeling, etc. can be well suppressed near the step difference.
[0048] Hereinafter, the case where the first adhesive layer 12 of the present embodiment is composed of an active energy ray-curable acrylic adhesive is described. Such a first adhesive layer 12 can be composed of an adhesive, for example, which is formed by crosslinking (thermal crosslinking) a first adhesive composition (hereinafter sometimes referred to as "the first adhesive composition P1") containing a (meth)acrylate copolymer (A), a crosslinking agent (B) and an active energy ray-curable component (C). In addition, the first adhesive composition P1 preferably further contains a photopolymerization initiator (D) as required. In addition, in this specification, (meth)acrylic acid refers to both acrylic acid and methacrylic acid. Other similar terms are also the same. Furthermore, the concept of "copolymer" is also included in "polymer".
[0049] (1-1) (Meth)acrylate copolymer (A)
[0050] Preferably, the (meth)acrylate copolymer (A) contains a reactive group-containing monomer having a reactive group that reacts with the crosslinking agent (B) in the molecule as a monomer unit constituting the polymer. Thus, the reactive group from the reactive group-containing monomer can react with the crosslinking agent (B). By introducing the monomer into the (meth)acrylate copolymer (A), it is easy to adjust the gel fraction or storage modulus of the resulting adhesive.
[0051] Preferred examples of the reactive group-containing monomer include monomers having a hydroxyl group in the molecule (hydroxyl group-containing monomers), monomers having a carboxyl group in the molecule (carboxyl group-containing monomers), monomers having an amino group in the molecule (amino group-containing monomers), etc. Among them, hydroxyl group-containing monomers are particularly preferred because they have excellent reactivity with the crosslinking agent (B) and have little adverse effect on the adherend.
[0052] As the hydroxyl-containing monomer, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and the like (meth)acrylate hydroxyalkyl esters and the like can be cited. Among them, 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate is preferred from the viewpoint of the reactivity of the hydroxyl group in the obtained (meth)acrylate copolymer (A) with the crosslinking agent (B) and the copolymerizability with other monomers. The above-mentioned hydroxyl-containing monomers can be used alone or in combination of two or more.
[0053] From the perspective of increasing the gel fraction or storage modulus of the obtained adhesive to the desired degree, the (meth)acrylate copolymer (A) preferably contains 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and further preferably 12% by mass or more of hydroxyl-containing monomers as monomer units constituting the polymer, based on the following limit. In addition, from the perspective of decreasing the gel fraction or storage modulus of the obtained adhesive to the desired degree, based on the upper limit, the (meth)acrylate copolymer (A) preferably contains 30% by mass or less, particularly preferably 25% by mass or less, and further preferably 20% by mass or less of hydroxyl-containing monomers as monomer units constituting the polymer.
[0054] The (meth)acrylate copolymer (A) can impart a preferred storage modulus to the obtained adhesive and exhibit preferred adhesion by containing a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms as a monomer unit constituting the polymer. Examples of (meth)acrylate alkyl esters having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearic (meth)acrylate. Among them, from the perspective of making the storage modulus suitable and further improving the adhesion, (meth)acrylates having an alkyl group with 4 to 8 carbon atoms are preferred, and 2-ethylhexyl (meth)acrylate is particularly preferred. The above-mentioned alkyl (meth)acrylates may be used alone or in combination of two or more.
[0055] The (meth)acrylate copolymer (A) preferably contains 40% by mass or more, particularly preferably 50% by mass or more, and further preferably 60% by mass or more of a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms as a monomer unit constituting the polymer. Furthermore, it preferably contains 90% by mass or less, particularly preferably 80% by mass or less, and further preferably 70% by mass or less of a (meth)acrylate alkyl ester having an alkyl group with 1 to 20 carbon atoms.
[0056] It is also preferred that the (meth)acrylate copolymer (A) contains a monomer having an alicyclic structure in the molecule (alicyclic structure-containing monomer) as a monomer unit constituting the copolymer. It can be inferred that since the volume of the alicyclic structure-containing monomer is large, by making it present in the polymer, the spacing between the polymers can be enlarged, and the softness of the resulting adhesive can be excellent. By making the (meth)acrylate copolymer (A) contain alicyclic structure-containing monomers, even when the adhesive sheet 10 of the present embodiment is attached to an adherend having a step difference on the surface, the first adhesive layer 12 can also follow the step difference well when attached.
[0057] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a saturated structure or may have an unsaturated bond in a part. In addition, the alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. From the perspective of expanding the distance between the obtained (meth) acrylate copolymer (A) and effectively exerting the flexibility of the adhesive, it is preferred that the alicyclic structure is a polycyclic alicyclic structure (polycyclic structure). Further, considering the compatibility of the (meth) acrylate copolymer (A) with other components, it is particularly preferred that the polycyclic structure is a bicyclic to tetracyclic structure. In addition, from the perspective of effectively exerting the flexibility of the adhesive as described above, the carbon number of the alicyclic structure (referring to the total number of carbon atoms of the part forming the ring, when multiple rings exist independently, it refers to its total number of carbon atoms) is usually preferably 5 or more, and particularly preferably 7 or more. On the other hand, the upper limit of the carbon number of the alicyclic structure is not particularly limited, but from the perspective of the same compatibility as described above, it is preferably 15 or less, and particularly preferably 10 or less.
[0058] Examples of the above-mentioned alicyclic structure-containing monomer include cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. Among them, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate or isobornyl (meth)acrylate, which have better durability, are preferred, and isobornyl (meth)acrylate is particularly preferred. The above-mentioned alicyclic structure-containing monomers may be used alone or in combination of two or more.
[0059] When the (meth)acrylate copolymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, the (meth)acrylate copolymer (A) preferably contains 3% by mass or more, particularly preferably 5% by mass or more, and further preferably 8% by mass or more of the alicyclic structure-containing monomer. In addition, the (meth)acrylate copolymer (A) preferably contains 35% by mass or less, particularly preferably 25% by mass or less, and further preferably 15% by mass or less of the alicyclic structure-containing monomer as a monomer unit constituting the polymer.
[0060] It is also preferred that the (meth)acrylate copolymer (A) contains a monomer having a nitrogen atom in the molecule (nitrogen-containing monomer) as a monomer unit constituting the copolymer. In addition, the reactive group-containing monomer is not contained in the nitrogen-containing monomer. By making the nitrogen-containing monomer present in the polymer as a structural unit, the reaction of the acrylate copolymer (A) and the crosslinking agent (B) can be promoted, or polarity can be imparted to the adhesive, thereby improving the adhesion of the adhesive to polar surfaces such as glass surfaces.
[0061] Examples of the nitrogen atom-containing monomer include a monomer having a tertiary amino group, a monomer having an amide group, and a monomer having a nitrogen-containing heterocyclic ring. Among them, a monomer having a nitrogen-containing heterocyclic ring is preferred.
[0062] Examples of monomers having a nitrogen-containing heterocyclic ring include N-(methyl)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(methyl)acryloylpyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-(methyl)acryloylaziridine, aziridinylethyl(methyl)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide. Among them, N-(methyl)acryloylmorpholine is preferred, and N-acryloylmorpholine is particularly preferred, from the perspective of improving the cohesive force of the resulting adhesive and the blistering resistance in addition to the adhesion to polar surfaces such as glass surfaces.
[0063] When the (meth)acrylate copolymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, the (meth)acrylate copolymer (A) preferably contains 1% by mass or more, particularly preferably 2% by mass or more, and further preferably 5% by mass or more of the nitrogen atom-containing monomer. In addition, the (meth)acrylate copolymer (A) preferably contains 40% by mass or less, particularly preferably 25% by mass or less, and further preferably 15% by mass or less of the nitrogen atom-containing monomer as a monomer unit constituting the polymer.
[0064] As required, the (meth)acrylate copolymer (A) may also contain other monomers as monomer units constituting the polymer. As other monomers, it is preferred that monomers not containing reactive functional groups are used. As such other monomers, for example, (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, styrene, etc. may be cited. The above other monomers may be used alone or in combination of two or more.
[0065] The polymerization form of the (meth)acrylate copolymer (A) may be a random copolymer or a block copolymer.
[0066] According to the following limit, the weight average molecular weight of (meth) acrylate copolymer (A) is preferably more than 100,000, particularly preferably more than 200,000, and more preferably more than 300,000. By making the lower limit of the weight average molecular weight of (meth) acrylate copolymer (A) be above or above, the cohesive force of the obtained adhesive can be improved, the storage modulus and gel fraction of the adhesive can be prevented from becoming too low, and in addition, the adhesion can be prevented from becoming too high. In addition, according to the upper limit, the weight average molecular weight of (meth) acrylate copolymer (A) is preferably less than 1,000,000, particularly preferably less than 850,000, and more preferably less than 700,000. If the upper limit of the weight average molecular weight of (meth) acrylate copolymer (A) is below the above, the storage modulus and gel fraction of the obtained adhesive can be prevented from becoming too high, and in addition, the adhesion can be prevented from becoming too low. In addition, the weight average molecular weight in this specification is the value converted by standard polystyrene measured by gel permeation chromatography (GPC) method.
[0067] In the first adhesive composition P1, the (meth)acrylate copolymer (A) may be used alone or in combination of two or more.
[0068] (1-2) Cross-linking agent (B)
[0069] The crosslinking agent (B) can crosslink the (meth)acrylate copolymer (A) by heating the first adhesive composition P1 to form a good three-dimensional network structure. This further improves the cohesive force of the obtained adhesive and makes it easier to adjust the gel fraction and storage modulus to appropriate values.
[0070] As the crosslinking agent (B), any crosslinking agent that reacts with the reactive functional group of the (meth)acrylate copolymer (A) may be used, for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. Here, as described above, since the (meth)acrylate copolymer (A) preferably contains a hydroxyl-containing monomer as a structural monomer unit, it is preferred to use an isocyanate crosslinking agent having excellent reactivity with a hydroxyl group as the crosslinking agent (B). In addition, the crosslinking agent (B) may be used alone or in combination of two or more.
[0071] The isocyanate crosslinking agent contains at least a polyisocyanate compound. As the polyisocyanate compound, for example, aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, and the like, and biuret bodies and isocyanurate bodies of these substances, and further adducts as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil can be listed. Among them, from the perspective of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, and trimethylolpropane-modified toluene diisocyanate is particularly preferred.
[0072] Relative to 100 parts by mass of (meth) acrylate copolymer (A), the content of the crosslinking agent (B) in the first adhesive composition P1 is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more. In addition, relative to 100 parts by mass of (meth) acrylate copolymer (A), the content is preferably 3 parts by mass or less, particularly preferably 2 parts by mass or less, and more preferably 1 part by mass or less. By making the content of the crosslinking agent (B) within the above range, it is easy to adjust the gel fraction and storage modulus of the obtained adhesive to appropriate values.
[0073] (1-3) Active energy ray-curable component (C)
[0074] By making the first adhesive composition P1 contain an active energy ray curable component (C), the adhesive obtained by crosslinking (thermal crosslinking) the first adhesive composition P1 becomes an active energy ray curable adhesive. It is speculated that for this adhesive, the active energy ray curable component (C) is mutually polymerized by curing based on active energy ray irradiation after attaching the adherend, and the active energy ray curable component (C) after the polymerization is entangled in the crosslinked structure (three-dimensional network structure) of the (meth) acrylate copolymer (A). By forming the high-dimensional structure, it is easy to increase the gel fraction and storage modulus, while increasing the anchoring effect, and it is also easy to increase the adhesion.
[0075] The active energy ray-curable component (C) is not particularly limited as long as it is a component that is cured by irradiation with active energy rays and can obtain the above-mentioned effects, and can be any one of a monomer, an oligomer or a polymer, or a mixture thereof. Among them, preferably, a multifunctional acrylate monomer having excellent compatibility with the (meth)acrylate copolymer (A) and the like can be cited.
[0076] Examples of the polyfunctional acrylate monomer include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloyloxyethyl) isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, and the like. Functional type; trifunctional type such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, ε-caprolactone modified tri(2-(meth)acryloyloxyethyl)isocyanurate; tetrafunctional type such as diglycerol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate; pentafunctional type such as propionic acid modified dipentaerythritol penta(meth)acrylate; hexafunctional type such as dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, etc. Among the above, from the perspective of the step tracking property of the obtained adhesive under high temperature and high humidity conditions, di(acryloyloxyethyl)isocyanurate, tri(acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tri-(2-(methyl)acryloyloxyethyl)isocyanurate and other multifunctional acrylate monomers containing isocyanurate structures in the molecule are preferred, and multifunctional acrylate monomers with trifunctionality or more and containing isocyanurate structures in the molecule are more preferred. The above-mentioned multifunctional acrylate monomers can be used alone or in combination of two or more. In addition, from the perspective of compatibility with the (methyl)acrylate copolymer (A), it is preferred that the molecular weight of the multifunctional acrylate monomer is less than 1000.
[0077] From the perspective of easily increasing the gel fraction and the storage modulus, the content of the active energy ray-curable component (C) in the first adhesive composition P1 is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and particularly preferably 5 parts by mass or more, relative to 100 parts by mass of the (meth) acrylate copolymer (A), based on the following limit. In addition, relative to 100 parts by mass of the (meth) acrylate copolymer (A), based on the upper limit, the above content is preferably 50 parts by mass or less, more preferably 20 parts by mass or less, and particularly preferably 10 parts by mass or less.
[0078] (1-4) Photopolymerization initiator (D)
[0079] When ultraviolet rays are used as active energy rays for curing the active energy ray-curable adhesive, it is preferred that the first adhesive composition P1 further contains a photopolymerization initiator (D). By containing the photopolymerization initiator (D) as described above, the active energy ray-curable component (C) can be efficiently polymerized, and the polymerization curing time and the irradiation amount of the active energy ray can also be reduced.
[0080] Examples of such a photopolymerization initiator (D) include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-propane-1-one, and 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone. , benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo [2-hydroxy-2-methyl-1 [4- (1-methylvinyl) phenyl] acetone], 2,4,6-trimethylbenzoyl - diphenyl - phosphine oxide, etc. Among them, since sufficient curing reaction can be carried out across the resin plate containing the ultraviolet absorber, it is more preferable to use a phosphine oxide-based photopolymerization initiator. The above-mentioned photopolymerization initiator can be used alone or in combination of two or more.
[0081] The content of the photopolymerization initiator (D) in the first adhesive composition P1 is preferably 0.1 parts by mass or more, particularly preferably 1 part by mass or more, relative to 100 parts by mass of the active energy ray-curable component (C), based on the following limit. In addition, based on the upper limit, it is preferably 30 parts by mass or less, particularly preferably 15 parts by mass or less.
[0082] (1-5) Various additives
[0083] As required, various additives commonly used in acrylic adhesives may be added to the first adhesive composition P1, such as silane coupling agents, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index adjusters, etc. In addition, the polymerization solvent or dilution solvent described later is not included in the additives constituting the first adhesive composition P1.
[0084] Here, when the first adhesive composition P1 contains a silane coupling agent, the adhesion between the obtained adhesive and the glass member or the plastic plate is improved.
[0085] As the silane coupling agent, an organic silicon compound having at least one alkoxysilyl group in the molecule, good compatibility with the (meth)acrylate copolymer (A), and light-transmitting property is preferred.
[0086] Examples of the silane coupling agent include silicon compounds containing polymerizable unsaturated groups such as vinyl trimethoxysilane, vinyl triethoxysilane, and methacryloxypropyl trimethoxysilane; silicon compounds having epoxy structures such as 3-glycidyloxypropyl trimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane; and silicon compounds containing mercapto groups such as 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, and 3-mercaptopropyl dimethoxymethylsilane. Compounds; amino-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; 3-chloropropyltrimethoxysilane; isocyanatepropyltriethoxysilane; or condensates of at least one of these silane coupling agents and alkyl-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. The above-mentioned silane coupling agents may be used alone or in combination of two or more.
[0087] When the first adhesive composition P1 contains a silane coupling agent, the content thereof is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more, relative to 100 parts by mass of the (meth)acrylate copolymer (A). In addition, the content thereof is preferably 2 parts by mass or less, particularly preferably 1 part by mass or less, and further preferably 0.5 parts by mass or less, relative to 100 parts by mass of the (meth)acrylate copolymer (A).
[0088] (1-6) Preparation of the first adhesive composition
[0089] The first adhesive composition P1 can be prepared by preparing a (meth)acrylate copolymer (A), and mixing the obtained (meth)acrylate copolymer (A), a crosslinking agent (B), an active energy ray-curable component (C), a photopolymerization initiator (D), and additives as required.
[0090] The (meth)acrylate copolymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate copolymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof may be used simultaneously.
[0091] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid methyl ester), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0092] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0093] In the above-mentioned polymerization step, by blending a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.
[0094] After obtaining the (meth)acrylate copolymer (A), a crosslinking agent (B), an active energy ray curable component (C), a photopolymerization initiator (D), an additive and a diluent solvent are added to the solution of the (meth)acrylate copolymer (A) as needed, and the mixture is fully mixed to obtain a first adhesive composition P1 (coating solution) diluted with a solvent. In addition, for any of the above components, when a solid component is used or when precipitation occurs when mixed with other components in an undiluted state, the component can be dissolved alone or diluted in a diluent solvent in advance and then mixed with other components.
[0095] As the above-mentioned dilution solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and vinyl chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-type solvents such as ethyl cellosolve, etc. can be used.
[0096] The concentration and viscosity of the coating solution prepared in the above manner are not particularly limited as long as they are within the range that can be coated, and can be appropriately selected according to the circumstances. For example, the first adhesive composition P1 is diluted in a manner such that the concentration is 10 to 60% by mass. In addition, when obtaining the coating solution, it is not necessary to add a diluting solvent, etc. If the first adhesive composition P1 is a coating viscosity, etc., no diluting solvent may be added. At this time, the first adhesive composition P1 is a coating solution in which the polymerization solvent of the (meth)acrylate copolymer (A) is directly used as the diluting solvent.
[0097] (1-7) Physical Properties of the First Adhesive Layer
[0098] The thickness of the first adhesive layer 12 of the present embodiment can be appropriately set according to the purpose of the adhesive sheet 10. For example, the thickness is preferably 100 μm or more, more preferably 140 μm or more, particularly preferably 180 μm or more, and further preferably 200 μm or more. By making the thickness of the first adhesive layer 12 more than 100 μm, it is easy to achieve excellent step tracking. In addition, the above-mentioned thickness is preferably less than 1000 μm, particularly preferably less than 500 μm, and further preferably less than 300 μm. By making the thickness of the first adhesive layer 12 less than 1000 μm, it is easy and effective to suppress the generation of wrinkles in the adhesive sheet 1. In addition, the greater the thickness of the first adhesive layer 12, the greater the winding pressure of the first film 11 on the second film 13 caused by winding, and the higher the difficulty of suppressing wrinkles.
[0099] From the perspective of further reducing the generation of wrinkles, the storage modulus of the first adhesive layer 12 of the present embodiment at 23°C is preferably 0.001MPa or more, particularly preferably 0.01MPa or more, and more preferably 0.05MPa or more. In addition, the storage modulus is preferably 1.00MPa or less, more preferably 0.5MPa or less, particularly preferably 0.2MPa or less, and more preferably 0.09MPa or less. By making the storage modulus of the first adhesive layer 12 at 23°C the above-mentioned upper limit, even when the adhesive sheet 10 of the present embodiment is attached to an adherend having a step difference on the surface, the first adhesive layer 12 also follows the step difference better during the attachment. In addition, when the first adhesive layer 12 of the present embodiment is composed of the above-mentioned active energy ray-curable adhesive, unless otherwise specified, the above-mentioned storage modulus refers to the storage modulus before the first adhesive layer 12 is irradiated with active energy rays. In addition, the test method of the above-mentioned storage modulus is shown in the test example described later.
[0100] When the first adhesive layer 12 of the present embodiment is composed of the above-mentioned active energy ray-curable adhesive, the storage modulus of the first adhesive layer 12 at 23°C after irradiating the first adhesive layer 12 with active energy rays is preferably 0.01MPa or more, particularly preferably 0.06MPa or more, and further preferably 0.11MPa or more. In addition, the storage modulus is preferably 2MPa or less, more preferably 1MPa or less, particularly preferably 0.5MPa or less, and further preferably 0.32MPa or less. By making the storage modulus of the first adhesive layer 12 at 23°C after irradiation with active energy rays within the above range, the step tracking property of the first adhesive layer 12 under durable conditions is more excellent. In addition, the test method of the above-mentioned storage modulus is shown in the test example described later.
[0101] In addition, when the first adhesive layer 12 is composed of an active energy ray-curable adhesive, the ratio of the storage modulus at 23°C of the first adhesive layer 12 after irradiation with active energy rays to the storage modulus at 23°C of the first adhesive layer 12 before irradiation with active energy rays is preferably 1.1 times or more, particularly preferably 1.6 times or more, and further particularly preferably 1.9 times or more. On the other hand, the above ratio is preferably 10 times or less, more particularly preferably 5 times or less, and further preferably 3 times or less. By making the above ratio within the above range, the step tracking property of the first adhesive layer 12 under durable conditions is more excellent.
[0102] The gel fraction of the adhesive constituting the first adhesive layer 12 of the present embodiment is preferably 20% or more, particularly preferably 30% or more, and further preferably 40% or more. In addition, the gel fraction is preferably 80% or less, particularly preferably 70% or less, and further preferably 60% or less. By making the gel fraction of the adhesive constituting the first adhesive layer 12 the above-mentioned upper limit value, the adhesive has a moderate cohesive force. Thus, even when the adhesive sheet 10 of the present embodiment is attached to an adherend having a step difference on the surface, the first adhesive layer 12 follows the step difference better during the attachment. In addition, when the first adhesive layer 12 of the present embodiment is composed of the above-mentioned active energy ray-curable adhesive, unless otherwise specified, the above-mentioned gel fraction refers to the gel fraction before the first adhesive layer 12 is irradiated with active energy rays. In addition, the test method of the above-mentioned gel fraction is shown in the test example described later.
[0103] When the first adhesive layer 12 of the present embodiment is composed of the above-mentioned active energy ray-curable adhesive, the gel fraction of the adhesive constituting the first adhesive layer 12 after irradiating the first adhesive layer 12 with active energy rays is preferably 45% or more, particularly preferably 55% or more, and further preferably 65% or more. In addition, the gel fraction is preferably 95% or less, particularly preferably 85% or less, and further preferably 75% or less. By making the gel fraction at 23°C after the active energy ray irradiation of the first adhesive layer 12 within the above range, the cohesive force of the adhesive after the active energy ray irradiation is well improved. As a result, the step tracking property of the first adhesive layer 12 under durable conditions is more excellent. In addition, the test method of the above-mentioned storage modulus is shown in the test example described later.
[0104] (3) Second film
[0105] In the adhesive sheet roll 1 of the present embodiment, there is no particular limitation as long as the surface of the second film 13 on the first adhesive layer 12 side is not subjected to a peeling treatment. For example, the second film 13 may be composed of a resin sheet having a resin material as a main component, or may be composed of a paper material. As preferred examples of the resin sheet and paper material for constituting the second film 13, the above-mentioned materials as the material of the first film 11 can be cited.
[0106] As described above, in the adhesive sheet roll 1 of the present embodiment, the thickness of the first film 11 is preferably less than the thickness of the second film 13. From the perspective of easily satisfying this relationship, the thickness of the second film 13 is preferably 50 μm or more, particularly preferably 75 μm or more, and further preferably 100 μm or more. In addition, the thickness of the second film 13 is preferably 300 μm or less, particularly preferably 200 μm or less, and further preferably 150 μm or less.
[0107] The Young's modulus of the second film 13 at 23°C is preferably 0.01 GPa or more, more preferably 0.1 GPa or more, particularly preferably 1 GPa or more, and further preferably 3 GPa or more. In addition, the Young's modulus is preferably 20 GPa or less, particularly preferably 10 GPa or less, and further preferably 5 GPa or less. By making the Young's modulus of the second film 13 at 23°C to be 0.01 GPa or more, it is easy to resist the winding pressure from the first film 11 during winding and maintain the shape, and the adhesive sheet 10 can be effectively suppressed from wrinkling. In addition, by making the Young's modulus of the second film 13 at 23°C to be 20 GPa or less, the rigidity will not become too high and it is easy to wind.
[0108] (4) Second Adhesive Layer
[0109] As described above, the adhesive sheet 10 of the present embodiment is also preferably provided with a second adhesive layer 14 stacked on the side of the second film 13 opposite to the first adhesive layer 12, and a third film 15 stacked on the side of the second adhesive layer 14 opposite to the second film 13. At this time, the laminate of the second adhesive layer 14 and the third film 15 can serve as a protective film for protecting the second film 13. In addition, usually when the adhesive sheet further has a laminate of the second adhesive layer and the third film, as a component that can become the starting point of wrinkles, in addition to the above-mentioned second film, the third film is also added. Therefore, compared with the case of the laminate without the second adhesive layer and the third film, when there is the laminate, wrinkles are particularly easy to generate. However, according to the adhesive sheet winding body 1 of the present embodiment, even when the above-mentioned laminate is provided, wrinkles can be well suppressed on the adhesive sheet 10.
[0110] The adhesive constituting the second adhesive layer 14 is not particularly limited and can be appropriately selected according to the application. In particular, when the laminate of the second adhesive layer 14 and the third film 15 is used as the protective film, the adhesive constituting the second adhesive layer 14 is preferably an adhesive that is easy to achieve the adhesive force and storage modulus described below.
[0111] As the adhesive constituting the second adhesive layer 14, it can be any one of acrylic adhesive, silicone adhesive, rubber adhesive, urethane adhesive, polyester adhesive, polyvinyl ether adhesive, etc. In addition, the above-mentioned adhesive can be any one of emulsion type, solvent type or solvent-free type, and can also be any one of cross-linked type or non-cross-linked type. Further, the above-mentioned adhesive can be an active energy ray-curable adhesive, and can also be an inactive energy ray-curable adhesive. Among them, from the perspective of easily satisfying the adhesive force described later and the storage modulus described later, the adhesive constituting the above-mentioned second adhesive layer 14 preferably uses an acrylic adhesive of inactive energy ray curability.
[0112] When the adhesive constituting the second adhesive layer 14 of the present embodiment is an acrylic adhesive that is not curable by active energy rays, such a second adhesive layer 14 can be composed of, for example, an adhesive obtained by cross-linking (thermal cross-linking) a second adhesive composition (hereinafter sometimes referred to as "second adhesive composition P2") containing a (meth)acrylate copolymer (A) and a cross-linking agent (B).
[0113] As the (meth)acrylate copolymer (A) contained in the second adhesive composition P2, for example, the same components as the above-mentioned (meth)acrylate copolymer (A) contained in the first adhesive composition P1 can be used. It is particularly preferred that the (meth)acrylate copolymer (A) contained in the second adhesive composition P2 contains a reactive group-containing monomer having a reactive group that reacts with the crosslinking agent (B) in the molecule and an alkyl (meth)acrylate having 1 to 20 carbon atoms in the alkyl group as monomer units constituting the polymer. In this case, the obtained second adhesive layer 14 has the desired cohesive force and is easy to exert the desired adhesive force.
[0114] Preferred examples of the above-mentioned reactive group-containing monomer and (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group of the second adhesive composition P2 include the same components as the monomers of the first adhesive composition P1. In particular, the (meth)acrylic acid ester copolymer (A) contained in the second adhesive composition P2 preferably uses 4-hydroxybutyl (meth)acrylate as the reactive group-containing monomer, and preferably uses n-butyl (meth)acrylate as the (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group.
[0115] In the (meth)acrylate copolymer (A) of the second adhesive composition P2, preferably 0.1% by mass or more, particularly preferably 0.5% by mass or more, and further preferably 1.0% by mass or more of a hydroxyl-containing monomer is contained as a monomer unit constituting the polymer. In addition, the (meth)acrylate copolymer (A) preferably contains 30% by mass or less, particularly preferably 20% by mass or less, and further preferably 10% by mass or less of a hydroxyl-containing monomer as a monomer unit constituting the polymer.
[0116] Furthermore, in the (meth)acrylate copolymer (A) of the second adhesive composition P2, it is preferred that 60% by mass or more, particularly preferably 70% by mass or more, and further preferably 80% by mass or more of (meth)acrylate alkyl esters having 1 to 20 carbon atoms in the alkyl group are contained as monomer units constituting the polymer. In addition, the (meth)acrylate copolymer (A) preferably contains 99.9% by mass or less, particularly preferably 99.5% by mass or less, and further preferably 99.0% by mass or less of (meth)acrylate alkyl esters having 1 to 20 carbon atoms in the alkyl group as monomer units constituting the polymer. Thus, it is easy to adjust the storage modulus and adhesive force of the obtained second adhesive layer 14 to the ranges described below.
[0117] The weight average molecular weight of the (meth) acrylate copolymer (A) contained in the second adhesive composition P2 is preferably 600,000 or more, particularly preferably 900,000 or more, and more preferably 1.1 million or more. In addition, the weight average molecular weight is preferably 2 million or less, particularly preferably 1.7 million or less, and more preferably 1.4 million or less. By making the weight average molecular weight the above range, it is easy to adjust the storage modulus of the obtained second adhesive layer 14 and the gel fraction of the adhesive constituting the second adhesive layer 14 to the range described below.
[0118] The crosslinking agent (B) contained in the second adhesive composition P2 can be, for example, the same component as the (meth)acrylate copolymer (A) contained in the first adhesive composition P1. Among them, as the crosslinking agent (B) contained in the second adhesive composition P2, it is preferred to use an isocyanate crosslinking agent with excellent reactivity with hydroxyl groups, and it is particularly preferred to use a trimethylolpropane-modified aromatic polyisocyanate, and it is further preferred to use trimethylolpropane-modified toluene diisocyanate.
[0119] Relative to 100 parts by mass of (meth) acrylate copolymer (A), the content of the crosslinking agent (B) in the second adhesive composition P2 is preferably 0.5 parts by mass or more, particularly preferably 1.0 parts by mass or more, and more preferably 2.0 parts by mass or more. In addition, relative to 100 parts by mass of (meth) acrylate copolymer (A), the content is preferably 10 parts by mass or less, particularly preferably 7 parts by mass or less, and more preferably 5 parts by mass or less. By making the content of the crosslinking agent (B) the above range, it is easy to adjust the storage modulus of the obtained second adhesive layer 14 and the gel fraction of the adhesive constituting the second adhesive layer 14 to the range described below.
[0120] In addition, similarly to the first adhesive composition P1, various additives commonly used in acrylic adhesives may be added to the second adhesive composition P2 as needed. Preferred examples of such additives are the same as those that may be added to the first adhesive composition P1.
[0121] The second adhesive composition P2 can be prepared by preparing a (meth)acrylate copolymer (A), and mixing the obtained (meth)acrylate copolymer (A), a crosslinking agent (B), and additives as required. The preparation of the above-mentioned (meth)acrylate copolymer (A) can be carried out in the same manner as the (meth)acrylate copolymer (A) contained in the first adhesive composition P1.
[0122] The thickness of the second adhesive layer 14 of the present embodiment can be appropriately set according to the purpose of the adhesive sheet 10. For example, the thickness is preferably 3 μm or more, particularly preferably 5 μm or more, and more preferably 7 μm or more. In addition, the thickness is preferably 40 μm or less, particularly preferably 30 μm or less, and more preferably 20 μm or less. By making the thickness of the second adhesive layer 14 within the above range, it is easy to achieve the desired adhesive force.
[0123] The storage modulus of the second adhesive layer 14 at 23°C of the present embodiment is preferably 0.01MPa or more, particularly preferably 0.04MPa or more, and more preferably 0.09MPa or more. In addition, the storage modulus is preferably 3MPa or less, particularly preferably 1MPa or less, and more preferably 0.5MPa or less. By making the storage modulus of the second adhesive layer 14 at 23°C in the above range, it is easy to use the second adhesive layer 14 to suppress the deformation of the third film 15 caused by the winding pressure of the first film 11 and the second film 13, and it is easy to achieve the desired adhesion. In addition, the test method of the above storage modulus is shown in the test example described later.
[0124] The gel fraction of the adhesive constituting the second adhesive layer 14 of the present embodiment is preferably 60% or more, particularly preferably 80% or more, and further preferably 90% or more. In addition, the gel fraction is preferably 100% or less, particularly preferably 99% or less, and further preferably 95% or less. By making the gel fraction of the adhesive constituting the second adhesive layer 14 within the above range, the adhesive has good cohesive force. Thus, it has appropriate adhesion and is easy to suppress the generation of wrinkles caused by the third film 15 when winding. In addition, the test method of the above storage modulus is shown in the test example described later.
[0125] (5) Third membrane
[0126] The material of the third film 15 is not particularly limited, and may be composed of a resin sheet having a resin material as a main component, or may be composed of a paper material, similarly to the first film 11 or the second film 13. Preferred examples of the resin sheet and paper material used for the third film 15 include the above-mentioned materials used as the material of the first film 11.
[0127] In addition, as described above, the third film 15 can function as a protective film for protecting the second film 13 together with the second adhesive layer 14. At this time, from the perspective of suppressing peeling at the interface between the second adhesive layer 14 and the third film 15, the surface of the third film 15 on the second adhesive layer 14 side is preferably not subjected to peeling treatment.
[0128] The thickness of the third film 15 is preferably 50 μm or more, particularly preferably 75 μm or more, and further preferably 100 μm or more. By making the thickness of the third film 15 50 μm or more, the third film 15 can easily and effectively play the role of a protective film, and it is easy to suppress the generation of wrinkles. In addition, the thickness of the third film 15 is preferably 300 μm or less, particularly preferably 200 μm or less, and further preferably 150 μm or less. By making the thickness of the third film 15 300 μm or less, it is easy to wind the adhesive sheet 10.
[0129] The Young's modulus of the third film 15 at 23°C is preferably 0.01GPa or more, more preferably 0.1GPa or more, particularly preferably 1GPa or more, and further preferably 3GPa or more. In addition, the Young's modulus is preferably 20GPa or less, particularly preferably 10GPa or less, and further preferably 5GPa or less. By making the Young's modulus of the third film 15 at 23°C be 0.01GPa or more, wrinkles can be effectively suppressed in the adhesive sheet 10. In addition, by making the Young's modulus of the third film 15 at 23°C be 20GPa or less, the second film 13 can be suppressed from having excessive rigidity, and the adhesive sheet 10 can be easily wound.
[0130] (6) Core material
[0131] The core material 20 of the present embodiment has a cylindrical or cylindrical shape. In addition, the diameter of the core material 20 of the present embodiment is 180 mm or more. By making the diameter of the core material 20 180 mm or more, as described above, the adhesive sheet winding body 1 of the embodiment of the present application can unwind the adhesive sheet 10 with excellent appearance. From this perspective, the diameter of the core material 20 is preferably 220 mm or more, particularly preferably 260 mm or more, and further preferably 290 mm or more. On the other hand, the upper limit of the diameter of the core material 20, from the perspective of being able to further increase the number of windings of the adhesive sheet 10, is 800 mm or less, preferably 600 mm or less, and particularly preferably 400 mm or less.
[0132] The length of the core material 20 of the present embodiment (the length in the rotation axis direction when the adhesive sheet 10 is wound) is not particularly limited, but is preferably the same as or greater than the width of the adhesive sheet 10 .
[0133] The material constituting the core material 20 is not particularly limited as long as it has sufficient strength for winding the adhesive sheet 10, and conventionally known materials can be used. Examples of the material include metals, resins, wood, etc. Among these materials, resins are preferred, polyolefin resins are more preferred, and polypropylene is particularly preferred.
[0134] The Young's modulus of the core material 20 at 23°C is preferably 0.01 GPa or more, particularly preferably 0.1 GPa or more, and further preferably 0.3 GPa or more. In addition, the Young's modulus is preferably 500 GPa or less, more preferably 100 GPa or less, particularly preferably 10 GPa or less, and further preferably 1 GPa or less. By making the Young's modulus of the core material 20 at 23°C in the above range, the shape of the core material 20 can be well maintained even when the winding pressure of the adhesive sheet 10 is applied to the core material 20. In addition, the Young's modulus of the core material 20 at 23°C refers to a value measured according to JIS Z2241:2011.
[0135] (7) Others
[0136] In the adhesive sheet winding body 1 of the present embodiment, the number of windings of the adhesive sheet 10 can be more than 3 turns, and in particular, more than 10 turns. The inventor of the present application found that when the number of windings is more than 3 turns, the adhesive sheet 10 unwound from the adhesive sheet winding body 1 is prone to wrinkles. However, according to the adhesive sheet winding body 1 of the present embodiment, even when the number of windings is more than 3 turns, the generation of the above-mentioned wrinkles can be effectively suppressed. In addition, the upper limit of the above-mentioned number of windings can be appropriately set from the perspective of the required length and amount of the adhesive sheet 10 or the operability of the adhesive sheet winding body 1, for example, it can be less than 2000 turns, and in particular, it can be less than 1500 turns.
[0137] In addition, in the adhesive sheet roll 1 of the present embodiment, the width of the adhesive sheet 10 (the length in the direction parallel to the winding axis of the adhesive sheet roll 1) can be appropriately set according to the purpose, for example, the width can be 100 mm or more, especially 500 mm or more, and further 900 mm or more. In addition, the width can be 3000 mm or less, especially 2000 mm or less, and further 1500 mm or less.
[0138] 2. Physical properties of adhesive sheet
[0139] In the adhesive sheet 10 of the present embodiment, the adhesion of the laminate of the second film 13 and the first adhesive layer 12 to the soda-lime glass can be appropriately set according to the purpose of the adhesive sheet 10, for example, preferably more than 1N / 25mm, particularly preferably more than 15N / 25mm, and more preferably more than 40N / 25mm. In addition, the adhesion is preferably less than 100N / 25mm, particularly preferably less than 80N / 25mm, and more preferably less than 60N / 25mm. By making the adhesion be the above range, the laminate of the second film 13 and the first adhesive layer 12 can exert good adhesion to the adherend. In addition, even if the first adhesive layer 12 is placed under high temperature and high humidity conditions in a state attached to the adherend, it is easy to well suppress the generation of bubbles, floating, peeling, etc. near the step difference.
[0140] In addition, when the adhesive sheet 10 of the present embodiment has the second adhesive layer 14 and the third film 15, the adhesion of the laminate of the third film 15 and the second adhesive layer 14 to the soda-lime glass is preferably 0.01N / 25mm or more, particularly preferably 0.1N / 25mm or more, and more preferably 0.5N / 25mm or more. In addition, the adhesion is preferably 20N / 25mm or less, particularly preferably 10N / 25mm or less, and more preferably 3N / 25mm or less. By making the adhesion be the above range, the laminate of the third film 15 and the second adhesive layer 14 is easy to fit well with the second film 13, and when the laminate is used as a protective film, it is easy to complete its purpose well. Especially when winding and unwinding the adhesive sheet 10, and when using it (when the surface of the first adhesive layer 12 that is opposite to the second film 13 is attached to the adherend), it is easy to suppress the accidental peeling of the above-mentioned protective film. At the same time, at a stage where the protective film is no longer necessary, adverse effects on the second film 13 and the first adhesive layer 12 are suppressed, and peeling and removal are easily and satisfactorily performed.
[0141] The details of the above-mentioned test method of adhesive force are shown in the test examples described later.
[0142] In the adhesive sheet 10 of the present embodiment, the peeling force when peeling the first film 11 from the laminate of the first adhesive layer 12 and the second film 13 is preferably 2000mN / 25mm or less, more preferably 1000mN / 25mm or less, particularly preferably 500mN / 25mm or less, and further preferably 200mN / 25mm or less. By making the above-mentioned peeling force less than 2000mN / 25mm, it is easy to peel off the first film 11 from the adhesive sheet 10. In addition, the above-mentioned peeling force is preferably more than 10mN / 25mm, particularly preferably more than 50mN / 25mm, and further preferably more than 100mN / 25mm. By making the above-mentioned peeling force more than 10mN / 25mm, it is easy to suppress the accidental peeling of the first film 11.
[0143] In addition, when the adhesive sheet 10 of the present embodiment has the second adhesive layer 14 and the third film 15, the peeling force when the laminate of the third film 15 and the second adhesive layer 14 is peeled off from the second film 13 is preferably 3000mN / 25mm or less, particularly preferably 2000mN / 25mm or less, and further preferably 1000mN / 25mm or less. By making the above-mentioned peeling force below 3000mN / 25mm, it is easy to peel off the laminate of the third film 15 and the second adhesive layer 14 from the adhesive sheet 10. In addition, the above-mentioned peeling force is preferably more than 10mN / 25mm, particularly preferably more than 100mN / 25mm, and further preferably more than 200mN / 25mm. By making the above-mentioned peeling force above 10mN / 25mm, it is easy to suppress the accidental peeling of the laminate of the third film 15 and the second adhesive layer 14.
[0144] The details of the above peel force test method are shown in the test examples described later.
[0145] 3. Method for manufacturing adhesive sheet roll
[0146] The method for producing the adhesive sheet roll 1 of the present embodiment is not particularly limited as long as it includes winding the adhesive sheet 10 on the core material 20 with the first film 11 side facing the outside, and a conventionally known method can be adopted.
[0147] When the adhesive sheet 10 of the present embodiment has a layer structure of the first film 11 / first adhesive layer 12 / second film 13, as a manufacturing method of the adhesive sheet 10, if an example thereof is cited, first, a coating solution of the above-mentioned first adhesive composition P1 is applied on a single side of the first film 11 (when a stripping treatment is performed, on the surface subjected to the stripping treatment). The obtained coating film is heat-treated, and the first adhesive composition P1 is thermally cross-linked to form the first adhesive layer 12. Then, by laminating a single side of the second film 13 on the surface of the first adhesive layer 12 which is the opposite side to the first film 11, an adhesive sheet 10 having a layer structure of the first film 11 / first adhesive layer 12 / second film 13 can be formed. As required, the first adhesive layer 12 can also be aged. In addition, in the above-mentioned manufacturing method, the first film 11 and the second film 13 can be exchanged.
[0148] In addition, as described above, when it is difficult to form the first adhesive layer 12 having a desired thickness by a single coating of the coating solution, the first adhesive layer 12 can be formed in the following manner. That is, a laminated body having an adhesive layer formed on a process sheet is prepared, and the surface on the adhesive layer side of the laminated body and the surface on the adhesive layer side of the laminated body of the first film 11 and the adhesive layer prepared in the above manner are laminated, thereby forming the first adhesive layer 12 having a desired thickness. At this time, the process sheet is peeled off, and the second film 13 is laminated to the exposed surface of the exposed first adhesive layer 12, thereby obtaining the adhesive sheet 10. Alternatively, a laminate having an adhesive layer formed on a single surface of the second film 13 is prepared, and the surface on the adhesive layer side of the laminate is bonded to the surface on the adhesive layer side of the laminate of the first film 11 and the adhesive layer prepared in the above manner, thereby forming a first adhesive layer 12 having a desired thickness, and obtaining an adhesive sheet 10 in which the first film 11, the first adhesive layer 12 and the second film 13 are stacked in sequence.
[0149] As a method for applying the coating solution of the first adhesive composition P1, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be used.
[0150] On the other hand, the adhesive sheet 10 having the layer structure of the first film 11 / the first adhesive layer 12 / the second film 13 / the second adhesive layer 14 / the third film 15 can be manufactured, for example, in the following manner. First, a laminate having the layer structure of the first film 11 / the first adhesive layer 12 / the second film 13 is obtained by the above method. In addition, a laminate having the layer structure of the second adhesive layer 14 / the third film 15 is obtained. Then, the laminate having the layer structure of the second adhesive layer 14 / the third film 15 can be manufactured by attaching the surface of the second adhesive layer 14 side of the laminate having the layer structure of the first film 11 / the first adhesive layer 12 / the second film 13 to the surface of the second film 13 side of the laminate having the layer structure of the first film 11 / the first adhesive layer 12 / the second film 13.
[0151] The laminate having the layer structure of the second adhesive layer 14 / third film 15 can be manufactured, for example, in the following manner. First, a coating solution of the second adhesive composition P2 is applied to the release-treated surface of the release sheet, and the resulting coating film is heat-treated to thermally crosslink the second adhesive composition P2 to form the second adhesive layer 14. Then, by laminating a single surface of the third film 15 on the surface of the second adhesive layer 14 opposite to the release sheet, a laminate having the layer structure of the second adhesive layer 14 / third film 15 can be obtained in a state where the release sheet is laminated on the surface of the second adhesive layer 14.
[0152] By winding the adhesive sheet 10 manufactured as described above on the core material 20, an adhesive sheet roll 1 can be obtained. In this winding, the adhesive sheet 10 is wound on the core material 20 in a manner such that the surface on the first film 11 side of the adhesive sheet 10 is on the outside. In addition, the manufacture of the adhesive sheet 10 and the winding of the manufactured adhesive sheet 10 can also be carried out continuously. That is, the stacking of the layers constituting the adhesive sheet 10 can be carried out upstream in the flow direction, and the winding of the adhesive sheet 10 obtained by completing the stacking can be carried out downstream in the flow direction.
[0153] When the above-mentioned winding is performed, tension can be applied to the adhesive sheet 10. The tension is preferably 10N / m or more, particularly preferably 50N / m or more, and more preferably 100N / m or more. In addition, the tension is preferably 1000N / m or less, particularly preferably 800N / m or less, and more preferably 500N / m or less. By applying the tension in the above range while winding the adhesive sheet 10, it is easy to manufacture an adhesive sheet roll 1 that is not loose and is evenly wound.
[0154] 4. How to use the adhesive sheet roll
[0155] The adhesive sheet roll 1 of the present embodiment can use the unwound adhesive sheet 10 for a desired purpose. For example, according to the adhesive sheet roll 1 of the present embodiment, the adhesive sheet 10 unwound from the adhesive sheet roll 1 can be used as a process sheet to manufacture a predetermined product. Alternatively, according to the adhesive sheet roll 1 of the present embodiment, the adhesive sheet 10 unwound from the adhesive sheet roll 1 can be used as a material to manufacture a predetermined product.
[0156] Examples of products manufactured using the adhesive sheet 10 of the present embodiment as a material include display devices and semiconductor devices.
[0157] According to the adhesive sheet roll 1 of the present embodiment, it is possible to provide an adhesive sheet 10 that suppresses the generation of wrinkles, so by using such an adhesive sheet 10, a product with excellent appearance can be manufactured. In addition, depending on the position and other forms of the adhesive sheet 10 used, the presence or absence of wrinkles not only affects the appearance of the product, but sometimes also affects the performance of the product. In such a case, by using the adhesive sheet roll 1 of the present embodiment, a product with excellent performance can be manufactured. From this perspective, the adhesive sheet 10 of the present embodiment is suitable for use in the manufacture of display devices. In particular, when the display device has mini-LED or micro-LED inside, by using the adhesive sheet 10 of the present embodiment as an adhesive sheet that directly or indirectly covers the surface of the mini-LED or micro-LED, a display device with mini-LED or micro-LED having excellent performance can be manufactured.
[0158] The specific method of using the adhesive sheet roll 1 of the present embodiment is not particularly limited. For example, the adhesive sheet 10 is unwound from the adhesive sheet roll 1, and then the first film 11 is peeled off from the adhesive sheet 10, and the adhesive surface of the exposed first adhesive layer 12 is attached to the desired adherend. When the adhesive sheet 10 has the third film 15 and the second adhesive layer 14, the laminate of the third film 15 and the second adhesive layer 14 is peeled off from the second film 13 at a desired time. Among them, when the laminate of the third film 15 and the second adhesive layer 14 is provided as a protective film for protecting the second film 13, it is preferred to peel off the laminate at a stage where protection is no longer required.
[0159] As described above, when the first adhesive layer 12 is composed of an active energy ray-curable acrylic adhesive, the first adhesive layer 12 can be cured by irradiating the first adhesive layer 12 with active energy rays at a desired time after the adhesive sheet 10 is attached to the adherend. At this time, even if there is a step or unevenness on the surface of the adherend, the first adhesive layer 12 can fully follow the step or unevenness and achieve the desired cohesive force. Thus, even if the adhesive sheet 10 is placed under high temperature and high humidity conditions with the first adhesive layer 12 attached to the adherend, the generation of bubbles, floating, peeling, etc. near the step can be well suppressed.
[0160] The active energy ray irradiated to the first adhesive layer 12 is an active energy ray having an energy quantum among electromagnetic waves or charged particle beams, and specific examples thereof include ultraviolet rays and electron beams, etc. Among active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.
[0161] The ultraviolet irradiation can be performed using a high pressure mercury lamp, a fusion H lamp, a xenon lamp, etc. The ultraviolet irradiation amount is preferably 50 mW / cm 2 Above, 1000mW / cm 2 The amount of ultraviolet light is preferably 50 mJ / cm 2 More preferably, 80 mJ / cm 2 Above, particularly preferably 200 mJ / cm 2 In addition, the amount of ultraviolet light is preferably 10000 mJ / cm 2 Below, more preferably 5000mJ / cm 2 Below, particularly preferably 2000 mJ / cm 2 On the other hand, electron beam irradiation can be performed using an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably 10 krad or more and 1000 krad or less.
[0162] As described above, after the adhesive layer 12 composed of an active energy ray-curable acrylic adhesive is attached to the first display body component having a step, when the adhesive layer 12 is cured by irradiating the active energy ray, the adhesive layer 12 is in a state of following the step well, and the cohesive force of the adhesive layer 12 is improved. Thus, even when the adhesive layer 12 is placed under high temperature and high humidity conditions in a state of being attached to an adherend, the generation of bubbles, floating, peeling, etc. near the step can be well suppressed.
[0163] As a preferred method of using the adhesive sheet roll 1 of the present embodiment, a case where the adhesive sheet roll 1 is used in a method for manufacturing a display device including mini-LEDs will be described below.
[0164] The manufacturing method includes, for example, a pasting step, wherein after unwinding the adhesive sheet 10 from the adhesive sheet roll 1, the first film 11 is peeled off from the adhesive sheet 10, and the exposed surface of the exposed first adhesive layer 12 is pasted on a backlight having a plurality of mini-LEDs. The mini-LEDs may be disposed on the backlight in a state of being embedded in a predetermined resin.
[0165] Furthermore, it is also preferable that the manufacturing method includes a cutting step of cutting the adhesive sheet 10 into a predetermined shape (for example, a shape corresponding to the backlight) before the attaching step.
[0166] When the first adhesive layer 12 is composed of an active energy ray-curable adhesive, the production method preferably includes a curing step after the attaching step in which the first adhesive layer 12 is cured by irradiating the first adhesive layer 12 with active energy rays.
[0167] When the adhesive sheet 10 includes a laminate of the second adhesive layer 14 and the third film 15 , it is also preferable to include a peeling step of peeling the laminate of the second adhesive layer 14 and the third film 15 from the second film 13 after the attaching step or the curing step.
[0168] According to the manufacturing method described above, a display device including mini-LEDs having excellent performance can be manufactured.
[0169] The above-described embodiments are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above-described embodiments also encompasses all design changes or equivalents within the scope of protection of the present invention.
[0170] Example
[0171] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.
[0172] [Example 1]
[0173] 1. Formation of the first stack
[0174] By solution polymerization, 65 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of 4-acryloylmorpholine (N-acryloylmorpholine), 10 parts by mass of isobornyl acrylate and 15 parts by mass of 2-hydroxyethyl acrylate were copolymerized to prepare a (meth)acrylate copolymer (A1). The molecular weight of the (meth)acrylate copolymer (A1) was measured by the method described below, and the weight average molecular weight (Mw) was 600,000.
[0175] Here, the weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured using gel permeation chromatography (GPC) under the following conditions (GPC measurement).
[0176] <Measurement Conditions>
[0177] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8320
[0178] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION
[0179] TSK gel superH-H
[0180] TSK gel superHM-H
[0181] TSK gel superH2000
[0182] ·Test solvent: tetrahydrofuran
[0183] ·Measurement temperature: 40℃
[0184] 100 parts by mass (solid content conversion value, the same below) of the (meth)acrylate copolymer (A1) obtained in the above manner, 0.15 parts by mass of trimethylolpropane-modified toluene diisocyanate as a crosslinking agent (B), 5.0 parts by mass of ε-caprolactone-modified tris-(2-acryloyloxyethyl)isocyanurate as an active energy ray-curable component (C), 0.5 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide as a photopolymerization initiator (D), and 0.5 parts by mass of 3-glycidyloxypropyltrimethoxysilane as a silane coupling agent were mixed and stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of the first adhesive composition.
[0185] Using a knife coater, the coating solution of the first adhesive composition obtained in the above manner was applied to the release-treated surface of a release sheet (thickness: 75 μm, Young's modulus: 4.6 GPa) on which one side of a long polyethylene terephthalate film as the first film was subjected to release treatment using a silicone release agent. Then, the obtained coating film was heated at 110° C. for 3 minutes to dry it, and a plurality of dried coating films were further laminated by transfer printing to form a first adhesive layer with a thickness of 250 μm.
[0186] Then, a single surface of a long polyethylene terephthalate film (thickness: 100 μm, Young's modulus: 4.6 GPa) as a second film was bonded to the surface of the formed first adhesive layer opposite to the first film, thereby obtaining a first laminate consisting of the structure of first film / first adhesive layer / second film.
[0187] 2. Formation of the Second Laminated Body
[0188] 99 parts by mass of n-butyl acrylate and 1 part by mass of 4-hydroxybutyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylate copolymer (A2). The molecular weight of the (meth)acrylate copolymer (A2) was measured by the above method, and the weight average molecular weight (Mw) was 1.3 million.
[0189] 100 parts by mass (solid content conversion value, the same below) of the (meth)acrylate copolymer (A2) obtained in the above manner and 2.0 parts by mass of trimethylolpropane-modified toluene diisocyanate as a crosslinking agent (B) were mixed and stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of the second adhesive composition.
[0190] Using a knife coater, the coating solution of the second adhesive composition obtained in the above manner is applied to a single surface of a long strip of polyethylene terephthalate film (thickness: 100 μm, Young's modulus: 4.6 GPa) as the third film. Then, the obtained coating film is heated at 110°C for 1 minute to dry it. Further, on the surface of the coating film on the opposite side to the third film, a release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") to which a silicone release agent is applied to a single surface of the long strip of polyethylene terephthalate film is subjected to a release treatment, is attached, and then aged at room temperature for 7 days to obtain a second laminate consisting of a third film / second adhesive layer (thickness: 5 μm) / release sheet.
[0191] 3. Manufacturing of adhesive sheet
[0192] The release sheet was peeled off from the second laminate obtained in the above step 2, and the exposed surface of the second adhesive layer thus exposed was bonded to the surface on the second film side of the first laminate obtained in the above step 1. Thus, a long adhesive sheet (width: 1080 mm) consisting of the structure of first film / first adhesive layer / second film / second adhesive layer / third film was obtained.
[0193] 4. Production of adhesive sheet roll
[0194] The adhesive sheet obtained in the above-mentioned process 3 is wound on a cylindrical core material (polypropylene, Young's modulus: 0.7GPa) with a diameter (outer diameter) of 304.8mm. At this time, the adhesive sheet is wound in such a way that the third film side of the adhesive sheet is the inner side, and a tension of 200N / m is applied along the length direction of the adhesive sheet. In addition, the length of the wound adhesive sheet is set to 300m. Thus, an adhesive sheet winding body is obtained.
[0195] [Examples 2 to 8]
[0196] An adhesive sheet roll was produced in the same manner as in Example 1 except that the thickness of each of the first film, the first adhesive layer, the second film, the second adhesive layer, and the third film and the diameter of the core material were changed as shown in Table 1.
[0197] [Example 9]
[0198] By solution polymerization, 55 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of 4-acryloylmorpholine (N-acryloylmorpholine), 10 parts by mass of isobornyl acrylate and 25 parts by mass of 2-hydroxyethyl acrylate were copolymerized to prepare a (meth)acrylate copolymer (A3). The molecular weight of the (meth)acrylate copolymer (A3) was measured by the above method, and the weight average molecular weight (Mw) was 600,000.
[0199] An adhesive sheet roll was produced in the same manner as in Example 1 except that a coating solution of the first adhesive composition was prepared using the obtained (meth)acrylate copolymer (A3) and the coating solution was further used to form the first adhesive layer.
[0200] [Example 10]
[0201] Except having changed each thickness of a 2nd film and a 3rd film as shown in Table 1, it carried out similarly to Example 1, and produced the adhesive sheet roll body.
[0202] [Example 11]
[0203] By solution polymerization, 55 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of 4-acryloylmorpholine (N-acryloylmorpholine), 10 parts by mass of isobornyl acrylate and 25 parts by mass of 2-hydroxyethyl acrylate were copolymerized to prepare a (meth)acrylate copolymer (A4). The molecular weight of the (meth)acrylate copolymer (A4) was measured by the above method, and the weight average molecular weight (Mw) was 600,000.
[0204] 100 parts by mass of the obtained (meth)acrylate copolymer (A4), 2.0 parts by mass of trimethylolpropane-modified toluene diisocyanate as a crosslinking agent (B), and 0.5 parts by mass of 3-glycidyloxypropyltrimethoxysilane as a silane coupling agent were mixed and stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of the first adhesive composition.
[0205] An adhesive sheet roll was produced in the same manner as in Example 1 except that the first adhesive layer was formed using the coating solution of the obtained first adhesive composition.
[0206] [Comparative Example 1]
[0207] Except having changed the diameter of the core material as shown in Table 1, it carried out similarly to Example 1, and produced the adhesive sheet roll body.
[0208] [Test Example 1] (Measurement of storage modulus of adhesive layer)
[0209] The first adhesive layers prepared in the examples and comparative examples were stacked to prepare a laminate having a thickness of 3 mm. A cylinder having a diameter of 8 mm (height of 3 mm) was punched out from the obtained laminate having the first adhesive layer and used as a sample.
[0210] The storage modulus (G') (MPa) of the above samples was measured under the following conditions using a viscoelasticity tester (manufactured by REOMETRIC, product name "DYNAMIC ANALYZER") according to JIS K7244-6:1999 by the torsional shear method. The results are shown in Table 1 as the storage modulus of the first adhesive layer before ultraviolet irradiation (before UV irradiation).
[0211] Measuring frequency: 1Hz
[0212] Measurement temperature: 23°C
[0213] In addition, for the sample obtained in the same manner as above, ultraviolet rays were irradiated under the following conditions to cure the first adhesive layer constituting the sample. For the cured sample, the storage modulus (G') (MPa) was also measured in the same manner as above. The results are shown in Table 1 as the storage modulus of the first adhesive layer after ultraviolet irradiation (after UV irradiation).
[0214] <Ultraviolet irradiation conditions>
[0215] Use high pressure mercury lamp
[0216] Illuminance 200mW / cm 2 , light intensity 1000mJ / cm 2
[0217] ・UV illuminance / light meter used was "UVPF-A1" manufactured by Eye graphics Co., Ltd.
[0218] Furthermore, the storage elastic modulus (G′) (MPa) before ultraviolet irradiation was measured for the second pressure-sensitive adhesive layers prepared in Examples and Comparative Examples in the same manner as above. The results are also shown in Table 1.
[0219] [Test Example 2] (Measurement of gel fraction)
[0220] The first laminate (composed of the first film / first adhesive layer / second film) obtained in the embodiment and the comparative example was cut into a size of 80 mm × 80 mm, and the first adhesive layer was wrapped in a polyester mesh (mesh size 200), and its mass was weighed using a precision balance, and the mass of the above-mentioned mesh alone was subtracted to calculate the mass of the adhesive itself constituting the first adhesive layer. The mass at this time was recorded as M1.
[0221] Then, the adhesive wrapped by the polyester net was immersed in ethyl acetate at room temperature (23°C) for 24 hours. Then, the adhesive was taken out and air-dried for 24 hours in an environment of 23°C and 50% relative humidity, and further dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the net alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was recorded as M2.
[0222] The values of mass M1 and M2 obtained in the above manner were substituted into the calculation formula of gel fraction (%) = (M2 / M1) × 100 to calculate the gel fraction (%). The results are shown in Table 1 as the gel fraction (%) of the first adhesive layer before ultraviolet irradiation (before UV irradiation).
[0223] In addition, the gel fraction (%) of the first adhesive layer cured by ultraviolet irradiation under the ultraviolet irradiation conditions described in Test Example 1 was calculated in the same manner as above. The results are shown in Table 1 as the gel fraction (%) of the first adhesive layer after ultraviolet irradiation (after UV irradiation).
[0224] Furthermore, the gel fraction (%) before irradiation with ultraviolet rays was calculated in the same manner as above for the second pressure-sensitive adhesive layers prepared in Examples and Comparative Examples. The results are also shown in Table 1.
[0225] [Test Example 3] (Measurement of Adhesion Strength)
[0226] The first laminate (composed of the first film / first adhesive layer / second film) obtained in the embodiment and the comparative example was cut into a width of 25 mm and a length of 100 mm. Then, the first film was peeled off from the first laminate, and the exposed surface of the exposed second adhesive layer was attached to a soda-lime glass (manufactured by Nippon Sheet Glass Co., Ltd.) under an environment of 23°C and 50% RH, and an autoclave (manufactured by KURIHARA SEISAKUSHO Co., Ltd.) was used to pressurize at 0.5 MPa and 50°C for 20 minutes.
[0227] Then, the first adhesive layers of Examples 1 to 10 and Comparative Example 1 were irradiated with ultraviolet rays under the conditions described in Test Example 1 through the PET film to be cured.
[0228] Then, after being placed under the conditions of 23°C and 50% RH for 24 hours, the adhesive force (N / 25mm) was measured using a tensile tester (manufactured by ORIENTEC Co., Ltd., product name "TENSILON") at a peeling speed of 300 mm / min and a peeling angle of 180 degrees. The conditions not described here were measured in accordance with JIS Z0237:2009. The results are shown in Table 1.
[0229] In addition, the adhesive force (N / 25mm) of the second laminate (structure of the third film / second adhesive layer / release sheet) obtained in the examples and comparative examples was also measured in the same manner as above. However, the surface of the second adhesive layer attached to the soda-lime glass was set as the exposed surface of the second adhesive layer exposed by peeling off the release sheet from the second laminate, and the second adhesive layer was not irradiated with ultraviolet rays. The results are also shown in Table 1.
[0230] [Test Example 4] (Measurement of peeling force)
[0231] The adhesive sheets produced in Examples and Comparative Examples were cut into pieces of 100 mm in length and 25 mm in width. Then, the surface of the adhesive sheet on the first film side was fixed to a stainless steel plate to obtain a sample for measuring peel strength.
[0232] For the above-mentioned peeling force measurement sample, JIS Z0237:2009 was used as a reference, under a standard environment (23°C, 50% RH), a tensile tester (manufactured by ORIENTEC Co., Ltd., product name "TENSILON UTM-4-100") was used, with a peeling angle of 180° and a peeling speed of 0.3m / min, to measure the force when peeling the laminate of the third film and the second adhesive layer from the second film, and the force was used as the peeling force (mN / 25mm) of the interface between the second adhesive layer and the second film. The results are shown in Table 1.
[0233] Then, in the same manner as above, the laminate of the second film and the first adhesive layer was peeled off from the first film, and the force measured at this time was taken as the peeling force (mN / 25 mm) at the interface between the first adhesive layer and the first film.
[0234] [Test Example 5] (Evaluation of step followability)
[0235] UV curable ink (manufactured by TEIKOKU PRINTING INKSMFG.CO.,LTD., product name "POS-911SUMI") was screen printed on the surface of a glass plate (manufactured by NSG PRECISION, product name "CORNING Glass EAGLE XG", 90 mm long × 50 mm wide × 0.5 mm thick) in a frame shape (outer shape: 90 mm long × 50 mm wide, 5 mm wide) so that the coating thickness was 10 μm. Then, ultraviolet rays (80 W / cm 2 , 2 metal halide lamps, lamp height 15 cm, belt speed 10-15 m / min), the printed ultraviolet curing ink was cured to produce a stepped glass plate with a printed step (step height: 10 μm). Furthermore, a stepped glass plate with a step height based on printing changed to 5 μm was also produced.
[0236] On the other hand, a coating solution of the first adhesive composition prepared in the embodiment and the comparative example is applied to the release-treated surface of the first release sheet on which one side of the polyethylene terephthalate film has been release-treated using a silicone release agent using a scraper. The obtained coating film is dried by heating it at 110°C for 3 minutes to form a first adhesive layer. The thickness of the first adhesive layer formed at this time is made the same as the thickness of the first adhesive layer in the adhesive sheet roll of the embodiment and the comparative example. Then, the release-treated surface of the second release sheet on which one side of the polyethylene terephthalate film has been release-treated using a silicone release agent is attached to the surface of the formed first adhesive layer on the opposite side of the first release sheet, thereby obtaining a sample for evaluation.
[0237] The first film was peeled off from the obtained evaluation sample to expose the first adhesive layer, and the first adhesive layer was laminated on the two glass plates with step obtained by the above method using a laminator (manufactured by FUJIPLA Inc., product name "LPD3214") so that the first adhesive layer covered the entire frame-shaped printed surface. Further, the second film was peeled off from each first adhesive layer, and a single surface of the glass plate (without printed step) was bonded to the exposed surface of the exposed first adhesive layer.
[0238] Under the conditions of 50°C and 0.5MPa, the laminate having the structure of a glass plate with a step (height of the step: 10μm or 5μm) / first adhesive layer / glass plate (without printed step) obtained in the above manner was subjected to autoclave treatment for 30 minutes and placed under normal pressure, 23°C, and 50%RH for 24 hours. Then, under the same conditions as in Test Example 3, the first adhesive layer was irradiated with ultraviolet rays through the glass plate (without printed step) to cure the first adhesive layer.
[0239] Then, the printed film was stored at 85°C and 85%RH for 72 hours (durability test). Then, the presence of bubbles, floating, and peeling at the interface between the printed step and the cured first adhesive layer was visually confirmed, and the step followability was evaluated according to the following criteria. The results are shown in Table 1.
[0240] ⊚: When the height of the printed step was 10 μm and 5 μm, bubbles, floating and peeling did not occur.
[0241] ○: When the height of the printing step was 10 μm, at least one of bubbles, floating, and peeling occurred. However, when the height of the printing step was 5 μm, bubbles, floating, and peeling did not occur.
[0242] ×: When the height of the printed step was 10 μm and 5 μm, at least one of bubbles, floating, and peeling occurred.
[0243] [Test Example 6] (Evaluation of the appearance of adhesive sheet)
[0244] All adhesive sheets were unwound from the adhesive sheet rolls obtained from the embodiments and comparative examples 7 days after manufacture, and the appearance abnormalities such as creases and deformation wrinkles were confirmed by naked eyes within the entire length (300m), and the appearance of the adhesive sheet was evaluated according to the following benchmarks. The results are shown in Table 1. In addition, the "5m position" in the following benchmark refers to the position 5m away from the end of the core material side of the adhesive sheet in the unwinding direction of the adhesive sheet roll, and other similar expressions are the same. In addition, the above-mentioned appearance abnormality does not include the marks caused by the tape used to fix the adhesive sheet to the core material.
[0245] ◎: No abnormal appearance occurs at least between 5m and 300m.
[0246] ○: Although an abnormal appearance occurred between 0 m and 10 m, no abnormal appearance occurred between 10 m and 300 m.
[0247] △: Although an abnormality in appearance occurred between 0 m and 30 m, no abnormality in appearance occurred between 30 m and 300 m.
[0248] ×: Appearance abnormality occurred between 30 m and 300 m.
[0249]
[0250] As can be seen from Table 1, the adhesive sheet rolls obtained in Examples can unwind adhesive sheets having excellent appearance.
[0251] Industrial Applicability
[0252] The adhesive sheet roll of the present invention is suitable for use in, for example, the manufacture of a display device, and is particularly suitable for use in the manufacture of a backlight including mini-LEDs or micro-LEDs as a light source included in a display device.
Claims
1. An adhesive sheet roll, comprising: a long adhesive sheet including a first film, a first adhesive layer laminated on one side of the first film, a second film laminated on the side of the first adhesive layer opposite to the first film, a second adhesive layer laminated on the side of the second film opposite to the first adhesive layer, and a third film laminated on the side of the second adhesive layer opposite to the second film, the long adhesive sheet being wound around a cylindrical or cylindrical core material in such a manner that the surface on the first film side faces the outside, the adhesive sheet roll being characterized in that: The diameter of the core material is greater than 230.2 mm and less than 304.8 mm. The thickness of the first adhesive layer is not less than 100 μm and not more than 1000 μm. The thickness of the first film is less than the thickness of the second film, The thickness of the third film is not less than 50 μm and not more than 300 μm, When the laminate of the third film and the second adhesive layer is peeled off from the second film, the peeling force is 10 mN / 25 mm or more and 3000 mN / 25 mm or less. The surface of the second film on the first adhesive layer side is not subjected to release treatment.
2. The adhesive sheet roll according to claim 1, wherein: The peeling force when the first film is peeled off from the laminate of the first adhesive layer and the second film is 10 mN / 25 mm or more and 2000 mN / 25 mm or less.
3. The adhesive sheet roll according to claim 1, wherein: The laminate of the third film and the second adhesive layer has an adhesive force to soda-lime glass of not less than 0.01 N / 25 mm and not more than 20 N / 25 mm.
4. The adhesive sheet roll according to claim 1, wherein: The storage modulus of the first adhesive layer at 23° C. is 0.001 MPa or more and 1.00 MPa or less.
Citation Information
Patent Citations
Silver recovering method
JP1983001027A
Method for storing layered product
JP1999109131A
Calculation system, calculation method, winding method, and wound roll body
JP2018169372A